Perlidae (Insecta: Plecoptera) da Serra do Roncador: região leste do Estado do Mato Grosso, Brasil - Deprá, Vanessa [UNESP] (2015)
Plecoptera is a small order of aquatic insects with approximately 3500 described species, distributed in 16 families. In Brazil, there are only two families Gripopterygidae and Perlidae. Among the genera occurring in Brazil, we highlight the genus Anacroneuria, which includes approximately 10% of the described species of the order. In this work, we study the fauna of Plecoptera from Serra do Roncador in order to contribute to the knowledge of fauna by the description of new species and the documentation of new geographic records. Three genera of Perlidae, Anacroneuria, Macrogynoplax e Enderleina were recorded. Among these genera, only adults of Anacroneuria were collected. Nine species of Anacroneuria were recorded from Serra do Roncador, Mato Grosso, Brazil, including a new species, which is described here